I suoni del calligrafo. Per un’analisi della drammaturgia sonora dello Jakob von Gunten di Fabio Condemi - Soldà, Valerio (Kritik. Rivista di letteratura e critica culturale, 2024)
This essay aims to illustrate the complexity of the phono-theatrical device put in place by Fabio Condemi for the construction of the sound dramaturgy of his play and the importance that the latter assumes for the construction of meanings within the entire performance. Beneath its surface, the spectator, digging in, can find the dialogue between Walser’s novel-which, as the remarks in the previous paragraph suggest, also carries with it the author’s entire universe, including his biography-and the mind of the director who read that novel in order to draw from it his performance. The viewer thus has access to the mechanisms that led to the genesis of the work and can treat what it manifests on its surface – here the sound dramaturgy created by Condemi – as a true signifying productivity, constantly evolving during the performance. A true engine of the play, in short, the sound body of Fabio Condemi’s Jakob von Gunten could not leave the stage without bringing with it a relevant part of the dramaturgy of the entire performance.